2016
DOI: 10.5430/jnep.v6n10p16
|View full text |Cite
|
Sign up to set email alerts
|

Stress perception, lifestyle behaviors, and emotional intelligence in undergraduate nursing students

Abstract: Background: The ongoing curricular changes in nursing programs have resulted in a marked increase in the stress experience of nursing students. Lifestyle behaviors are recognized as essential components of stress reduction and wellbeing. These behaviors include consuming a healthy diet, engaging in exercise, and seeking social support. Emotional intelligence (EI) was also included because of its positive effects on subjective well-being and its mitigating effects on stress. The purpose of this study was to exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 26 publications
0
6
1
Order By: Relevance
“…Lifestyle behaviors are considered essential components that influence well-being and health. Dietary habits, regular physical exercise, and religiosity/spirituality are major factors associated with these behaviors [ 29 ]. Therefore, we firstly compared the healthy lifestyle behaviors and dietary habits between the priests ( n = 10) and the age-matched non-priest controls ( n = 10).…”
Section: Resultsmentioning
confidence: 99%
“…Lifestyle behaviors are considered essential components that influence well-being and health. Dietary habits, regular physical exercise, and religiosity/spirituality are major factors associated with these behaviors [ 29 ]. Therefore, we firstly compared the healthy lifestyle behaviors and dietary habits between the priests ( n = 10) and the age-matched non-priest controls ( n = 10).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, we have also found that middle-aged women performing higher academic results develop better self-care levels, and these students also obtained more powerful scores in their SOC, as the findings of the major systematic review on the SOC in nurses suggest [ 74 ]. More investigations report that those students showing strong SOC values are more resistant to stress, keep healthier behaviours, show higher professional engagement, and, furthermore, theoretical assumptions determine that they do better academically [ 75 , 76 , 77 , 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nurses/nursing students, who integrate EI and social intelligence into health care realize how they can cope with their own emotions, how these emotions are affected by the social environment, and how these emotions affect the social environment. A nurse with these qualifications not only provides emotional support to healthy/unhealthy individuals and their families in clinical and field environments, where learning is multidimensional, but also guides them on how to cope with their emotional burden (Ali and Ali 2016). Emotional intelligence, which strengthens nursing care, is equally important in improving an individual's skills and problem-solving abilities (Kaya et al, 2017;Lee and Noh 2017).…”
Section: Introductionmentioning
confidence: 99%